Evaluation of naked oat accessions from the VIR collection for their qualitative characteristics in Kazakhstan - A. I. Abugalieva; I. G. Loskutov; T. V. Savin; V. A. Chudinov (Труды по прикладной ботанике, генетике и селекции)
Background. The grain of naked oat varieties has a unique biochemical composition (increased content of protein, starch, fat, and β-glucans) for the production of high-quality dietary food and feed. Relatively low adaptability restrains the spread of naked oat cultivars, but the demand for them has been increasing from year to year. Currently, only hulled oat cultivars are introduced into industrial cultivation in Kazakhstan, so the breeding trend aimed at the development of high-yielding naked oat cultivars may be regarded as a priority.Materials and methods. Thirty-five accessions of naked oats (Avena  sativa L.  subsp. nudisativa (Husnot.) Rod. et Sold.) were selected from the germplasm collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) for their suitability for the conditions in Kazakhstan in terms of the growing season, drought resistance and grain productivity. The study was carried out in 2015–2017 in the fields of the Kazakh Research Institute of Agriculture and Crop Production (Almaty) and the Karabalyk Agricultural Experimental Station (Kostanay). Grain quality of naked oats was assessed by various methods according to a set of biochemical characters: the content of protein and its fractions, starch, amylose, fat and fatty acids, and β-glucans.Results. The study of naked oat accessions from VIR in the environments of the southeastern Kazakhstan showed higher average values of protein content in grain than under the conditions in the north. As a result of the study, naked oat accessions with increased and stable indicators of the content of protein, starch, amylose, fat, individual fatty acids and β-glucans were identified for the conditions of the southeastern and northern regions of Kazakhstan. All selected accessions will be used in breeding programs of the Republic of Kazakhstan to develop high-yielding and high-quality naked oat cultivars.